Differential Performance of Wheat Genotypes for Grain Yield, Phosphorus Uptake and Utilization at Low and High Phosphorus: Evaluation of PUE in wheat genotypes - Abbas, Muhammad; Irfan, Muhammad; Shah, Javaid Ahmed (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
A pot experiment was conducted to test grain yield response and phosphorus use efficiency (PUE) in 10 wheat genotypes at low (10 mg P kg−1 soil) and high (40 mg P kg−1 soil) soil phosphorus (P) levels. The genotypes differed significantly (P < 0.05) for grain yield, P uptake and P efficiency indices at each P level. Phosphorus stress factor (PSF) varied between 0.15 and 30.1%, signifying the differential P responsiveness of the wheat genotypes. Each parameter was assigned an index score of 1, 2, or 3 for its low, medium, or high grade of performance at each P level. Furthermore, the genotypes were grouped into six categories based on their grain yield and total P uptake at low P level. Genotypes EST-28/11 and MSH-3 with high grain yield (8.42 and 7.95 g pot−1) and high P uptake (38.0 and 30.9 mg P pot-1), and NIA-Sunder with high grain yield (8.33 g pot-1) but medium P uptake (23.9 mg P pot-1) at low P level can be selected for P deficient soils. Genotypes EST-28/11, MSH-3 and NIA-Sunder also attained high total index scores (25, 23 and 23) at low P level. Such type of categorization will aid in breeding programs for improving nutrient use efficiency.